A political career for the Internet generation - O. V. Kryshtanovskaya; I. A. Lavrov (Цифровая социология)
The article deals with the problem of studying social mobility and classifying “social lifts” in the political sphere. The high relevance of this topic today is due to the growing politicisation of young people, as the result of this the social exclusion of young people is formed. Young people have a strong opinion that “social lifts” don’t exist or work. So young people sublimate their political energy in a protest activity unable to express their positions and interests legally.This article analysed both the political values of contemporary youth based on in-depth interviews (collective and individual) with 164 members of the young generation between the ages of 18 and 30, and the vertical mobility channels known from biographies of successful politicians at federal, regional and municipal levels. By this approach the typical positions from which a political career starts, the “entry points” into politics for newcomers have been identified, the valid mechanisms and institutions for upward mobility have been classified, and links with other career aspects have been revealed.The biographies of 800 officials and deputies throughout Russia (in eight federal districts) have been used and the career trajectories of representatives of government and local authorities have been analysed in the study. The classification of “social lifts” has been presented, their effectiveness and prevalence has been revealed, and links between education, profession, work experience and socio-demographic characteristics have been established.